Contributors to Racial Disparities in Minimally Invasive Hysterectomy in the US Department of Veterans Affairs. Issue 12 (December 2019) - Katon, Jodie G.; Bossick, Andrew S.; Doll, Kemi M.; Fortney, John; Gray, Kristen E.; Hebert, Paul; Lynch, Kristine E.; Ma, Erica W.; Washington, Donna L.; Zephyrin, Laurie; Callegari, Lisa S.
Abstract : Background: Minimally invasive hysterectomy for fibroids decreases recovery time and risk of postoperative complications compared with abdominal hysterectomy. Within Veterans Affair (VA), black women with uterine fibroids are less likely to receive a minimally invasive hysterectomy than white women. Objective: To quantify the contributions of patient, facility, temporal and geographic factors to VA black-white disparity in minimally invasive hysterectomy. Research Design: A cross-sectional study. Subjects: Veterans with fibroids and hysterectomy performed in VA between October 1, 2012 and September 30, 2015. Measures: Hysterectomy mode was defined using ICD-9 codes as minimally invasive (laparoscopic, vaginal, or robotic-assisted) versus abdominal. The authors estimated a logistic regression model with minimally invasive hysterectomy modeled as a function of 4 sets of factors: sociodemographic characteristics other than race, health risk factors, facility, and temporal and geographic factors. Using decomposition techniques, systematically substituting each white woman's characteristics for each black woman's characteristics, then recalculating the predicted probability of minimally invasive hysterectomy for black women for each possible combination of factors, we quantified the contribution of each set of factors to observed disparities in minimally invasive hysterectomy. Results: Among 1255 veterans with fibroids who had a hysterectomy at a VA, 61% of black women and 39% of white women had an abdominal hysterectomy. Our models indicated there were 99 excess abdominal hysterectomies among black women. The majority (n=77) of excess abdominal hysterectomies were unexplained by measured sociodemographic factors beyond race, health risk factors, facility, and temporal or geographic trends. Conclusion: Closer examination of the equity of VA gynecology care and ways in which the VA can work to ensure equitable care for all women veterans is necessary. Abstract : Supplemental Digital Content is available in the text.